The multiple meanings of EU law: using sociological interpretivism to make sense of the Eurozone crisis - Nicholas Haagensen (European Law Open)
In following the interdisciplinary spirit of this symposium, I emphasise the usefulness of the sociological approach of interpretivism, together with qualitative methods, by examining how EU legal actors perceived the Eurozone crisis and how they enabled policy solutions: financial assistance and policy conditionality. This case constitutes a legal conundrum because of how these solutions encompass and connect different forms of law – EU law, international law and private financial law – and how EU lawyers seek to protect the EU legal order from this hybrid arrangement by drawing the arrangement as closely as they can to the EU legal order. This in turn creates issues of accountability as the imposition of policy conditionality engenders litigation by EU citizens who were directly affected therein, raising the question of whether establishing liability for damages is possible in such a hybrid arrangement. Using interviews with legal actors and observations of court proceedings, I foreground the multiple meanings of EU law and explain how such an approach can expand our understanding of not only what EU law means to its practitioners, but also how these meanings give insight into the potential paths of EU law’s development. To interrogate these multiple meanings, I examine the crisis policy solutions as well as a set of court cases – Ledra Advertising, Mallis and Chrysostomides – that sought to hold the EU accountable for losses suffered because of these policies. Using these methods can partially overcome the opaqueness of judicial proceedings at the EU level, as well as give insight into the development of the legal arrangements being contested in court. A novel methodological element is the descriptive analysis of observations of court proceedings in Chrysostomides, where I demonstrate how the interactions between the lawyers and the judges shed light on how legal actors establish legal validity as a collective project.